Cheese-making without rennet - Technical Centre for Agricultural and Rural Cooperation (Technical Centre for Agricultural and Rural Cooperation, 1989)
In Nigeria and some other parts of Africa juice from the plant Calotropis procera is being used to coagulate milk for cheesemaking where rennet is difficult or expensive to obtain on a commercial scale. Calotropis procera (or 'kinbo') is a common...